Preliminary hypothetical assessment and in silico molecular docking of statin to VEGFR2 and VEGFR3 protein complex associated with angiogenesis and lymphangiogenesis in diabetic wounds - Divya Pamu, Selvaraj Ayyamperumal, Munikumar Manne, Vyshnavi Tallapaneni, Chandrasekar Joghee Nanjan Moola, Veera Venkata Satyanarayana Reddy Karri (Journal of Applied Pharmaceutical Science, 2023)
Vascular endothelial growth factor (VEGF) receptors are the critical drivers for blood vessel formation and lymphangiogenesis in diabetic wounds. However, due to the high blood glucose levels, advanced glycation end products release inflammatory mediators, which lead to hypoxic conditions that decrease the synthesis of essential growth factors and degeneration of the blood vessels necessary for the recovery of the diabetic wound. Hence, repurposing statins and identifying the binding potential to the active amino acid residues on the vascular endothelial growth factor receptor (VEGFR 2) and VEGFR 3 receptor could be a preliminary analysis and hypothetical computational challenge that statins can bind to VEGFs. That initiates the VEGF levels and reduces the inflammation associated with the conversion of M2 macrophages. Hence VEGFR 2 and VEGFR 3 are promising therapeutic targets for starting angiogenesis and lymphangiogenesis in diabetic wounds. Furthermore, the statins (Atorvastatin, Fluvastatin, Lovastatin, Pitavastatin, Pravastatin, Rosuvastatin, and Simvastatin) subjected to computational molecular docking (Lib docking), and the best statins are selected based on the LibDock score and hydrogen and hydrophobic bond interactions. The results revealed that Atorvastatin (125.90 and 126.0), Fluvastatin (126.37 and 120.0), Pravastatin (129.90 and 128.6), and Rosuvastatin (130.01 and 130.62 ) had shown a significant binding potential to VEGFR2 and VEGFR3 protein complex and more excellent LibDock score with less variation when compared with the remaining statin molecules. Furthermore, the selected molecules were subjected to computational pharmacophore modeling and toxicity studies. The pharmacophore modeling was carried out to identify the feature set amino acids between the ligand and protein complex, followed by hypothetical confirmation of toxicity when the statin molecules interact with the skin tissue to determine carcinogenicity and skin sensitivity. The toxicity studies revealed that the four statins molecules showed moderate to less skin sensitivity and non-carcinogenicity. In addition, they have demonstrated different solubility parameters computationally. The preliminary hypothetical analysis can be a computational proof for further targeting statins (Atorvastatin, Fluvastatin, Pravastatin, and Rosuvastatin) to VEGFR2 and VEGFR3 for promoting angiogenesis and lymphangiogenesis in diabetic wounds. Taking these evidence-based docking results could provide a future pathway to carry out further research characterization and evaluation of statins for treating and managing diabetic wounds.